The Relationship of Speaking Anxiety, Motivation, and Self-Confidence with Students’ Speaking Performance of Grade X at Vocation High School - Brilianti Sastra Winda; Siswana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aimed to investigate the relationships between speaking anxiety, motivation, self-confidence, and students’ speaking performance among Grade X students at SMK Jakarta Barat 1. The study employed a quantitative correlational research design involving 53 students selected through cluster sampling. The data were collected using questionnaires and speaking tests. The questionnaires were used to measure students’ speaking anxiety, motivation, and self-confidence, while the speaking test assessed students’ speaking performance based on fluency, accuracy, pronunciation, vocabulary, and comprehension. The data were analyzed using descriptive statistics, Pearson Product-Moment Correlation, and Multiple Linear Regression Analysis with the assistance of SPSS version 25. The findings revealed that speaking anxiety had a significant negative relationship with students’ speaking performance (r = -0.412, p = 0.002), indicating that students with higher anxiety levels tended to demonstrate lower speaking performance. In contrast, self-confidence showed a significant positive relationship with speaking performance (r = 0.370, p = 0.006), suggesting that students with higher self-confidence tended to perform better in speaking activities. Meanwhile, motivation showed a low positive correlation with speaking performance (r = 0.202, p = 0.148), but the relationship was not statistically significant. Furthermore, the regression analysis indicated that speaking anxiety and self-confidence were significant predictors of students’ speaking performance, whereas motivation was not significantly related to speaking performance. These findings indicate that psychological variables are associated with students’ speaking performance, particularly speaking anxiety and self-confidence. The study contributes to the understanding of psychological factors in English as a Foreign Language (EFL) speaking contexts by highlighting the importance of reducing speaking anxiety and strengthening students’ self-confidence to support better speaking performance.